PENGARUH PENGGUNAAN KULIT PISANG BIOKONVERSI DALAM RANSUM TERHADAP PERFORMANS AYAM BROILER - Nur Adiva Situmorang; B. Sukamto; E. Suprijatna (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2016)
This research was aimed to determaine the influence of banana peel bioconvertion in the diet on protein utilization of broiler chicken. The experiment used 120 broiler chickens at 14 days old unsex with average body weight 475 ± 0,98 g. Feed rations were consist of 22% crude protein; 3200 kcal/kg metabolizable energy. Completely randomized design with 4 treatments and 6 replication was used in this experiment which T0 (control): rations without banana peel bioconvertion, T1: ration with banana peel bioconvertion 5%, T2: ration with banana peel bioconvertion10%, T3: ration with seaweedbanana peel bioconvertion15%. Feed provided ad libitum until this research until from 14-35 day old. The data obtained were analyzed using Analysis of Variance (ANOVA) F-test with level 5% and if the result of the analysis showed significant effect of treatment will be followed by Duncan's test with SPSS 16 program. The results showed that treatment banana peel bioconvertion showed non significant effect of performance.